The Effects of Macroeconomic Variables on the BIST 100 Index: ARDL and NARDL Approaches - Mohammed Algoni; Mehmet İvrendi (International Journal of Public Finance)
The objective of this research is to analyze the signal, magnitude, and significance of both symmetric and asymmetric effects of interest rate, taxes, exchange rate, oil price, and gold price on the Turkish stock market (BIST100). The autoregressive distributed lag (ARDL) technique was used in both linear and non-linear formats. The F-Bounds test of the linear ARDL test suggests that the variables do not exhibit long-term integration. Nevertheless, the F-bounds test of the nonlinear ARDL (NARDL) test confirms the presence of cointegration among the variables. Therefore, the research heavily relies on the NARDL model. The empirical evidence indicates the long-term influence of the exchange rates rate, gold price, and interest rate on the BIST100 index is asymmetric. Additionally, the asymmetrical effects of interest rates, taxes, exchange rates, oil prices, and gold prices in the short term have an impact on the BIST100.